Coordination-assembled myricetin nanoarchitectonics for sustainably scavenging free radicals - Ma, Xiaoyan; Gong, Haoning; Ogino, Kenji; Yan, Xuehai; Xing, Ruirui (Beilstein Journal of Nanotechnology, 2022)
Oxidative stress can lead to permanent and irreversible damage to cellular components and even cause cancer and other diseases. Therefore, the development of antioxidative reagents is an important strategy to alleviate chronic diseases and maintain the redox balance in cells. Small-molecule bioactive compounds have exhibited huge therapeutic potential as antioxidants and anti-inﬂammatory agents. Myricetin (Myr), a well-known natural flavonoid, has drawn wide attention because of its high antioxidant, anti-inflammatory, antimicrobial, and anticancer efficacy. Especially regarding antioxidation, Myr is capable of not only chelating intracellular transition metal ions for removing reactive oxygen species, but also of activating antioxidant enzymes and related signal pathways and, thus, of sustainably scavenging radicals. However, Myr is poorly soluble in water, which limits its bioavailability for biomedical applications, and even its clinical therapeutic potential. The antioxidant peptide glutathione (GSH) plays a role as antioxidant in cells and possesses good hydrophilicity and biocompatibility. However, it is easily metabolized by enzymes. To take advantages of their antioxidation activity and to overcome the abovementioned limitations, GSH, Zn2+, and Myr were selected to co-assemble into Myr-Zn2+-GSH nanoparticles or nanoarchitectonics. This study oﬀers a new design to harness stable, sustainable antioxidant nanoparticles with high loading capacity, high bioavailability, and good biocompatibility as antioxidants.
Keywords: antioxidant; co-assembly; glutathione; myricetin; nanoarchitectonics